Life-span of Classical Solutions to Nonlinear Wave Equations in Two-space-dimensions II (Journal of Partial Differential Equations, 1993)
In two-space-dimensional case we get the sharp lower bound of the life-span of classical solutions to the Cauchy problem with small initial data for fully nonlinear wave equations of the form &#x25fbu = F (u, Du, D_zDu) in which F(\hat{&#955}) = O(|\hat{&#955}|^{1+&#945}) with &#945 = 2 in a neighbourhood of \hat{&#955} = 0. The cases &#945 = 1 and &#945 &#8805 3 have been considered respectively in [1] and [2].
Keywords: Life-span; classical solution; Cauchy problem; nonlinear wave equation